Peran Pemerintah Desa Margasari dalam Meningkatkan Pelayanan Administrasi Kependudukan (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to describe the village government's strategy in improving administrative competency in Margasari Village and to identify the obstacles and challenges faced as well as the opportunities and potential that can be utilized by the Margasari Village government in overall village services. The research method used is qualitative with a descriptive approach. The research was conducted at the Margasari Village Office located on Jl. Buyut Baka Margasar, Puloampel District, Serang Regency, Banten with an estimated research period from September 2024 to April 2025. In data collection, this study uses observation, interviews and documentation as well as Triangulation. Meanwhile, in data analysis, the stages used are data reduction, data presentation and drawing conclusions. The results of this study indicate that the Margasari Village Government Apparatus has implemented a strategy in the form of training, socialization and coaching programs for both its own apparatus and the community, but the implementation has not been fully optimal because there are still obstacles and barriers that occur from providing efficient population administration services offline and online. With these problems, the potential and opportunities that are utilized are by optimizing training for officers to improve their competence in the digitalization realm so that even with limited facilities and budget, services can still be optimized by utilizing sophisticated technology and the availability of existing facilities.